2015
DOI: 10.1210/jc.2015-1110
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Women With Primary Hyperparathyroidism

Abstract: Serum calcium levels are usually only mildly elevated during pregnancy in women with PHPT. A significant proportion of cases go undiagnosed. Mild hypercalcemia in gestational PHPT is generally not associated with an increased risk of obstetrical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 25 publications
9
89
4
3
Order By: Relevance
“…found that it occurred in 0.03% of reproductive age women who underwent routine screening of serum calcium (391). Several hundred cases have been described in English-language medical journals (354,391,466), while the author's advice has been sought for several cases each year by clinicians around the globe.…”
Section: Mineral Metabolism During Pregnancy and Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…found that it occurred in 0.03% of reproductive age women who underwent routine screening of serum calcium (391). Several hundred cases have been described in English-language medical journals (354,391,466), while the author's advice has been sought for several cases each year by clinicians around the globe.…”
Section: Mineral Metabolism During Pregnancy and Lactationmentioning
confidence: 99%
“…Several hundred cases have been described in English-language medical journals (354,391,466), while the author's advice has been sought for several cases each year by clinicians around the globe. Primary hyperparathyroidism is 10 -20 times more likely to occur in women over age 45 than in women of child-bearing age (373,980), but in two case series, ϳ1% of all parathyroidectomies were done in pregnant women (466,490).…”
Section: Mineral Metabolism During Pregnancy and Lactationmentioning
confidence: 99%
“…Denosumab might represent an alternative to bisphosphonates in controlling severe hypercalcaemia as (69). In a recent series of 74 mild PHPT women aged 20-40 years who experienced pregnancy, kidney stones were reported in 12% of patients (70).…”
Section: Effects Of Bisphosphonates On Kidney Functionmentioning
confidence: 99%
“…Hypercalcemia in pregnancy is uncommon, occurring in approximately 0.03% of women of reproductive age 1. The condition is probably underdiagnosed due to its nonspecific symptomalogy and the physiological decrease in total calcium accompanying lower albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of hypercalcemia in pregnancy is primary hyperparathyroidism (PHPT) 1, 9. Most of the data in the literature on hypercalcemia in pregnancy come from women with PHPT.…”
Section: Discussionmentioning
confidence: 99%